2004
DOI: 10.1002/adma.200304906
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oriented and Ordered Arrays from Block Copolymers via Solvent Evaporation

Abstract: tion of individual protein molecules or complexes than an extended, homogeneous surface. Of course, this hypothesis needs to be tested by biological activity. ExperimentalSize-selected metal (Au) clusters, with size between 1 and 100 atoms, were generated by an RF (radio-frequency) magnetron sputtering, gas condensation [20,21] cluster beam source and mass selected to within 5 % by a novel, lateral time-of-flight mass filter to control the cluster size, as described previously [22]. The energetic beam of ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
1,073
5
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 918 publications
(1,105 citation statements)
references
References 31 publications
21
1,073
5
6
Order By: Relevance
“…In the past decade, electric fields, 6 temperature gradients, 7 directional solidification, 8 modification of substrate surfaces, 9 shearing, 10 solvent evaporation, 11 and roll casting 12 These responses should help achieve nanostructure control. Liquid crystalline (LC) rod-coil block copolymers are good candidates because they respond to multiple stimuli including electric and magnetic fields, temperature and light (if the mesogen is a chromophore).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, electric fields, 6 temperature gradients, 7 directional solidification, 8 modification of substrate surfaces, 9 shearing, 10 solvent evaporation, 11 and roll casting 12 These responses should help achieve nanostructure control. Liquid crystalline (LC) rod-coil block copolymers are good candidates because they respond to multiple stimuli including electric and magnetic fields, temperature and light (if the mesogen is a chromophore).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, it has recently been demonstrated that diblock/triblock copolymer films based on poly(styrene-bethylene oxide) (PSt-b-PEO) and poly(styrene-b-methyl methacrylate-b-ethylene oxide) (PSt-b-PMMA-b-PEO) exhibited cylindrical microdomains with a high degree of lateral ordering after solvent annealing under controlled humidity conditions. [26][27][28] In these examples, no neutralization layer is required, and it is believed that the relative humidity plays an important role in a lateral ordering of the block copolymer thin films, presumably by a strong interaction between the water vapor and the hydrophilic PEO domains during the solvent annealing process. 26 While such a process does not work directly with PSt-b-PMMA block copolymers, it is an intriguing possibility if a similar lateral ordering and vertical orientation can be induced in these hydrophobic systems by simple introduction of "external" hydrophilic moieties into PSt-b-PMMA copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] This neutralization layer is not required for poly(ethylene oxide) (PEO)-based block copolymer systems where the morphologies and orientation of the thin films are controlled and greatly affected by the relative humidity during a solvent annealing process, though removal of the PEO domain is difficult. [25][26][27][28] In this case, it was found that interaction between the water vapor in the atmosphere and the PEO domains leads to lateral ordering of the PEO microdomains, and application of this process to PSt-b-PMMA systems did not lead to orientation. In this paper, we demonstrate a novel method to control the orientation of PSt-b-PMMA block copolymer thin films using hydrophilic nanoparticles without the need for a neutralization layer, greatly improving the processability of PSt-b-PMMA systems.…”
Section: Introductionmentioning
confidence: 99%
“…5,18,19 Some studies have also shown that the orientation of microphase-separated structures can be controlled by exposing block copolymer films to solvent vapor and drying at a controlled evaporation rate. 13,18,[20][21][22][23][24][25][26][27] We have reported the experimental visualization of a threedimensional (3D) helical morphology for a polystyrene-block-polybutadiene-block-poly(methyl methacrylate) triblock terpolymer (SBM) using transmission electron microtomography (TEMT). 28 The TEMT observations revealed that the double-helical structure was composed of polybutadiene (PB) helical microdomains around hexagonal-packed polystyrene (PS) cylinder cores in a poly(methyl methacrylate) (PMMA) matrix, even though the block copolymer was not chiral.…”
Section: Introductionmentioning
confidence: 99%